Profile of High School Students' Critical Thinking Skills and Problem-Solving Abilities in Static Fluid Materials - Ardian Fachreza; Andhy Setiawan; Muslim (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to describe the profile of high school students' critical thinking skills and problem-solving abilities in static fluid materials. A descriptive quantitative design was employed, involving 85 eleventh-grade students. Data were collected using essay tests based on Ennis’s and Heller and Heller’s indicators, then analyzed using descriptive statistics. The results revealed that students' critical thinking skills were moderate (mean: 67.01), with high proficiency in focusing on questions (97.35%) but severe weaknesses in deduction (53.24%) and induction (51.18%). Conversely, problem-solving abilities were very low (mean: 39.58), with all operational stages scoring poorly, particularly in evaluating solutions (25.65%). The study concludes that while students excel at surface-level information extraction, they experience significant cognitive bottlenecks in higher-order reasoning, physical representation, and systematic solution planning. Consequently, physics instruction must transition from procedural calculation to explicit, staged scaffolding that integrates multi-representation, scientific argumentation, and metacognitive evaluation.